Analyzing Curriculum Management in Facing the Implementation of the Independent Learning Curriculum - Zuhdi, Moh Irham; Huda, Muhammad; Arifin, Imron; Baadal, Ibrahim (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
The Ministry of Education, Culture, Research, and Technology has a policy called Analyzing Curriculum Management in Facing the Implementation of the Independent Learning Curriculum that intends to maximize the management of the currently employed curriculum. The purpose of this study is to examine curriculum management in light of the adoption of the Independent Learning Curriculum. Teachers and school principals implement the Independent Learning curriculum through the use of a case study approach in the research methodology. The data for this study was gathered through observation, documentation, and interviews and followed by analysis through the gathering, processing, presenting, and drawing of data. The results are rather empirical. According to this study, teachers are perfectly prepared to apply the curriculum for autonomous learning. The lack of knowledge of the independent learning curriculum between instructors and parents is a barrier that teachers face while implementing curriculum management in order to face the implementation of the curriculum. Additionally, the infrastructure and amenities are insufficient.